An assessment of the Mi-Mark endoemtrial sampling technique. Issue 1 (January 1980) - Crow, J; Gordon, H; Hudson, E
Abstract : One hundred and twenty cytological smears and 106 histological specimens were obtained from 115 patients using a new technique of endometrial sampling. It proved an atraumatic procedure and was well accepted by the patients. Some problems were encountered in the preparation of satisfactory cytological specimens and in their interpretation. The method was not completely reliable for detecting endometrial pathology and is therefore considered unsuitable for monitoring patients on hormone replacement therapy. It was found to be useful as a gynaecological outpatient technique for sampling the endometrium when formal curettage was unsuccessful, in avoiding the necessity for a preoperative curettage to confirm suspected carcinoma, and in the investigation of infertility.